Spontaneous orbital meningoencephalocele and temporal encephalocele: An odd cause of proptosis and seizure, a case report and literature review - S. El Graini; H. Retal; S. Habib Chorfa; N. Ech-Cherif El Kettani; M. Fikri; M. Jiddane; F. Touarsa (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Meningoencephaloceles (MEC) of the skull base commonly result from head trauma, or congenital malformation, or may arise spontaneously due to increased intracranial pressure, leading to a bony defect and subsequent herniation of brain parenchyma. Spontaneous MEC at orbital and temporal locations are rare, with only a few cases reported in the literature. Brain MRI is typically used for diagnosis, and treatment may be medical or surgical, depending on the size of the bony defect. We present an unusual case of a 69-year-old woman with spontaneous orbital and temporal MEC, resulting in proptosis, strabismus, and seizures secondary to idiopathic intracranial hypertension (IIH). This condition was managed medically, with a favourable outcome. This report aims to describe and analyse the case, reviewing the literature on spontaneous MEC in adult patients at different locations caused by IIH and their management, emphasizing the critical role of imaging in diagnosing this etiology.